Modelling of the microencapsulation of betacyanins and their antioxidant activity extracted from red amaranth - Chong, Pik Han; Yusof, Yus Aniza; Aziz, Mohammad Gulzarul; Chin, Nyuk Ling; Naim, Mohd Nazli; Mohd Rosdan, Faridatul Ain (2012)
Betacyanin is a type of betalain responsible for red or violet color and can be found in the family Amaranthus gangeticus. This water-soluble natural pigment can be extracted using water extraction and spray drying was involved to produce pigment powder. The objective of the study is to optimize and model the spray drying process using response surface methodology with independent variables of spray drying inlet temperature and maltodextrin concentration, responses would be betacyanin retention and antioxidant activity. Results for response of betacyanin retention from ANOVA test showed linear terms of inlet temperature and carrier concentration and their interaction were no significant differences (P > 0.05) for betacyanin retention. However there were significant differences (P <0.05) in quadratic terms. The value of R2(Adj) for the above equation is 0.62. It indicates that the correlation between the observed and predicted values is very poor. For antioxidant activity, the linear for the factor of inlet temperature and quadratic terms of both inlet temperature and the ratio of core/coating material, as well as their interaction did not show significant differences (P > 0.05) on antioxidant activity. However, significant differences (P < 0.05) were observed for linear term of carrier concentration. In conclusion, the predictive model established between the betacyanin retention and the factors; inlet temperature and maltodextrin concentration was verified and found adequate for the model.